Gender-dependent language anxiety in Polish communication apprehensives - Piechurska-Kuciel, Ewa (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2012)
This paper analyzes the relationship between communication apprehension and language anxiety from the perspective of gender. As virtually no empirical studies have addressed the explicit influence of gender on language anxiety in communication apprehensives, this paper proposes that females are generally more sensitive to anxiety, as reflected in various spheres of communication. For this reason, language anxiety levels in communication apprehensive females should be higher, unlike those of communication apprehensive males. Comparisons between them were made using a student t test, two-way ANOVA, and post-hoc Tukey test. The results revealed that Polish communication apprehensive secondary grammar school males and females do not differ in their levels of language anxiety, although nonapprehensive males experience significantly lower language anxiety than their female peers. It is argued that the finding can be attributed to developmental patterns, gender socialization processes, classroom practices, and the uniqueness of the FL learning process, which is a stereotypically female domain.
Keywords: communication apprehension; apprehensives; language anxiety; Gender